2018
DOI: 10.1371/journal.pone.0196083
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the eight GABAA receptor α subunits in the developing zebrafish central nervous system

Abstract: GABA is a robust regulator of both developing and mature neural networks. It exerts many of its effects through GABAA receptors, which are heteropentamers assembled from a large array of subunits encoded by distinct genes. In mammals, there are 19 different GABAA subunit types, which are divided into the α, β, γ, δ, ε, π, θ and ρ subfamilies. The immense diversity of GABAA receptors is not fully understood. However, it is known that specific isoforms, with their distinct biophysical properties and expression p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 59 publications
3
29
0
Order By: Relevance
“…Over the course of development the expression of gabra1 became more restricted to the midbrain-hindbrain regions (Fig. 2) consistent with previously published work (Monesson-Olson et al, 2018; Samarut et al, 2018).…”
Section: Resultssupporting
confidence: 91%
“…Over the course of development the expression of gabra1 became more restricted to the midbrain-hindbrain regions (Fig. 2) consistent with previously published work (Monesson-Olson et al, 2018; Samarut et al, 2018).…”
Section: Resultssupporting
confidence: 91%
“…Over the course of development the expression of gabra1 became more restricted to the midbrainhindbrain regions (Fig. 2), consistent with previously published work (Monesson-Olson et al, 2018;Samarut et al, 2018).…”
Section: Expression Patterns Of the Zebrafish Ortholog Of Gabra1supporting
confidence: 90%
“…Published data suggest that within broad brain divisions implicated in regulating stress (e.g. telencephalon, diencephalon), α 1 -, α 2 -, and γ 2 -subunits of GABA A R showed similar expression across individuals in the telencephalon and olfactory bulbs, but were more variable within the diencephalon 84 86 . While studies have demonstrated differences in GABAergic neurons and GABA A R neurons across broad divisions of the zebrafish brain 84 86 , to our knowledge no study has mapped and quantified GABA A R distribution at the resolution of individual brain nuclei in zebrafish.…”
Section: Discussionmentioning
confidence: 99%